Analisis Faktor-Faktor yang Memengaruhi Perilaku Pengguna Google Apps for Education Menggunakan Information Boundary Theory (IBT) dan Technology Acceptance Model (TAM) (Studi Pada Universitas XYZ) - Harin Puspa Ayu Catherina; Ari Kusyanti; Retno Indah Rokhmawati (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Google Apps for Education is a suite of apps with real time synergies and collaborations between students, faculty and staff on campus accessible using PC computers, notebooks, tablets and even smartphones. To be able to be enjoy a range of services from Google Apps For Education, a user is required to have a Google Apps For Education account. In the process of registration of a new Google account, a user will always be asked some data related to the user's identity. As a big company that highly values the privacy of users, Google Apps For Education includes a privacy policy that contains about how Google uses data that has been shared by its user and the reason why Google Apps For Education needs to ask some users' private data. The object of this study is to analyze the behavior of users regarding Google Apps For Education. Data collected from users of Google Apps for Education services by 300 respondents. SEM is used as data analysis method with 10 construct variables. The results of this study indicate that the factors that affect the user's intention to use Google Apps for Education is Perceived Usefulness and Perceived Ease of Use.